Suksesi Areal Bekas Ladang Berpindah Di Desa Sungai Buluh, Kalteng - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT Degraded forest land in Indonesia was estimated at about several ten-millions ha. According to FAO report in 1990, about 23 millions ha were bushy vegetation and 20 millions ha were bare/critical lands and alang-alang formations. It is, therefore, necessary to study ecological changes of these land in order to make proper land management and forest management. This paper employs statistical ecology to analyze ecological changes in degraded forest land caused by slash-and-burn practices. The results show that species diversity, based on species richness and evenness, is increasing and becoming more stable from time to time. Species diversity is represented by the effective number of species present in a sample. Explicitly, it consisted of three effective numbers of species in the sample: NO (thenumber of all species), Ni (the number of abundant species) and N2 (the numlier of very abundant of species). The relationship among the three effective numbers of species give good information about the changes of species evenness in the community. The rarefraction method is a useful technique for not only comparing species evenness but also defining the number of species in different sample size. It is argued that more advanced studies including ecological, economical analyses about utilizing the degraded forest land are needed.